Industry unbound : the inside story of privacy, data, and corporate power - Waldman, Ari Ezra, 1980- (Cambridge : Cambridge University Press, 2021)
In Industry Unbound, Ari Ezra Waldman exposes precisely how the tech industry conducts its ongoing crusade to undermine our privacy. With research based on interviews with scores of tech employees and internal documents outlining corporate strategies, Waldman reveals that companies don't just lobby against privacy law; they also manipulate how we think about privacy, how their employees approach their work, and how they weaken the law to make data-extractive products the norm. In contrast to those who claim that privacy law is getting stronger, Waldman shows why recent shifts in privacy law are precisely the kinds of changes that corporations want and how even those who think of themselves as privacy advocates often unwittingly facilitate corporate malfeasance. This powerful account should be ready by anyone who wants to understand why privacy laws are not working and how corporations trap us into giving up our personal information.
Introduction -- A day at the office -- Privacy's discourses -- Privacy compliance -- Designing data-extractive technologies -- Power, practice, and performance -- Fighting back -- Conclusion.
Title from publisher's bibliographic system (viewed on 22 Sep 2021).
Keywords: Data protection -- Law and legislation -- United States; Business ethics -- United States